Paradoxos da encarnação: por uma radicalização democrática da teologia política - Ramon Mapa da Silva (2019)
The aim of this thesis is to work the possibilities of development of a democratic and radical political theology. The political theology has been, until now, insufficiently political, but, mainly, insufficiently democratic. Even in its prime, that it can be found, undoubtly, in the work of Carl Schmitt, it is nothing but a way of theological legitimation and justification of the sovereignty. This process of legitimation also serves the religion of despair, of the endless cult, the capitalism. Even the Theology of Liberation and others theologies of the crisis that rose up in the XX Century were not able to escape from the minoic maze of the capitalist religion. A democratic and radical political theology has to be a theology of the common, openly against the Empire and against the Capitalism. It is a messianic theology, in the sense of Walter Benjamin, that aims the redemption and the happiness of the sufferer. A theology to the Multitude.